THE IMPLICATION OF APPLYING SQ3R TECHNIQUE TO THE STUDENTS’ READING ABILITY - Dede Imtihanudin (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2017)
SQ3R stands for survey, question, read, recite and review. It is step to learn and comprehend a content of text book or articles. The purpose of this research is to know whether the SQ3R technique could increase students reading ability. This research performed by using descriptive method and statistical approach which intended to reach and conclude this research problem. The populations of this research are 60 students and the writer took 25 students or around 42% as a sample of the research. As the instrument of collecting data writer took from documentation, observation, and questionnaire. The writer used 15 items of questionnaire to know X variable, and 25 question whereas to know Y variable. According to the data analysis the correlation between X and Y variable is 0,58 and the distribution variable is 33,44%, it means there are other factor can effect students reading ability around 66,56%. The above data calculation shows that SQ3R technique has already implicated in improving students reading achievement.